# Extensions 1→N→G→Q→1 with N=C2 and Q=C42⋊7S3

Direct product G=N×Q with N=C2 and Q=C427S3
dρLabelID
C2×C427S396C2xC4^2:7S3192,1035

Non-split extensions G=N.Q with N=C2 and Q=C427S3
extensionφ:Q→Aut NdρLabelID
C2.1(C427S3) = (C2×Dic6)⋊7C4central extension (φ=1)192C2.1(C4^2:7S3)192,488
C2.2(C427S3) = C4211Dic3central extension (φ=1)192C2.2(C4^2:7S3)192,495
C2.3(C427S3) = (C2×C4)⋊6D12central extension (φ=1)96C2.3(C4^2:7S3)192,498
C2.4(C427S3) = (C2×C42)⋊3S3central extension (φ=1)96C2.4(C4^2:7S3)192,499
C2.5(C427S3) = (C2×C4).17D12central stem extension (φ=1)192C2.5(C4^2:7S3)192,218
C2.6(C427S3) = C6.C22≀C2central stem extension (φ=1)96C2.6(C4^2:7S3)192,231
C2.7(C427S3) = (C22×S3)⋊Q8central stem extension (φ=1)96C2.7(C4^2:7S3)192,232
C2.8(C427S3) = (C2×C4).21D12central stem extension (φ=1)96C2.8(C4^2:7S3)192,233
C2.9(C427S3) = C12.14Q16central stem extension (φ=1)192C2.9(C4^2:7S3)192,240
C2.10(C427S3) = C4.5D24central stem extension (φ=1)96C2.10(C4^2:7S3)192,253
C2.11(C427S3) = C42.264D6central stem extension (φ=1)96C2.11(C4^2:7S3)192,256
C2.12(C427S3) = C42.14D6central stem extension (φ=1)192C2.12(C4^2:7S3)192,262
C2.13(C427S3) = C42.19D6central stem extension (φ=1)96C2.13(C4^2:7S3)192,272
C2.14(C427S3) = C42.20D6central stem extension (φ=1)96C2.14(C4^2:7S3)192,273

׿
×
𝔽